Insect Management for Sweet Corn - Gregg S. Nuessly; Susan E. Webb (EDIS)
This document is ENY-472 (which replaces ENY-449), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001. Revised: July 2003.